Aging and biography : explorations in adult development - Birren, James E. (Springer Pub. Co., 1996)
Personal life narratives can serve as a rich source of new insights into the experience of human aging. In this comprehensive volume, an international team of editors and contributors provide effective approaches to using biography to enhance our understanding of adult development. In addition to providing new theoretical aspects on aging and biography, the book also details new developments concerning the practical use of different biographical approaches in both research and clinical work. This is a landmark volume advancing the use of narrative approaches in gerontology.